Stethoscope barriers narrative review; It's time for a strategy unfriendly to multi-drug resistant organisms (MDROs) - W. Frank Peacock; Abhay Dhand; Nancy M. Albert; Zainab Shahid; Alfred Luk; Kathleen Vollman; Reagan B. Schoppelrey; Cynthia Cadwell; Sanjeet Dadwal; Alpesh N. Amin; Francesca J. Torriani (Elsevier, 2024)
The current standard of stethoscope hygiene doesn't eliminate the transmission of harmful pathogens, including multi-drug resistant organisms (MDROs). In the era of the increasing prevalence of MDRO infections, the use of new systems providing touch free barriers may improve patient safety versus traditional stethoscope cleaning practices with chemical agents. Our purpose was to provide a narrative literature review regarding barriers as an improvement over the current standard of care for stethoscope hygiene. Searching PubMed, articles were identified if they were in English and published after 1990, using the search term "stethoscope barrier", or if they were from a previously published stethoscope hygiene article using "author's name + stethoscope". Included articles evaluated or discussed stethoscope barriers. Of 28 manuscripts identified, 15 met the inclusion criteria. Barriers were considered superior to alternatives if they were single use, disposable, applied in a touch free fashion, were impervious to pathogens, provided an aseptic patient contact, and were acoustically invisible. Use of a practitioner's personal stethoscope with a disposable diaphragm barrier should be recommended as a new standard of care as this represents an improvement in patient safety and patient experience when compared to the disposable stethoscope or isopropyl alcohol stethoscope diaphragm cleaning.